Gram-Scale Synthesis of (R)-P-Chlorophenyl-1,2-Ethanediol at High Concentration by a Pair of Epoxide Hydrolases - Zhang, Dong; Lei, Yuqing; Wang, Tingting; Lin, Wenqian; Chen, Xingyi; Wu, Minchen (Frontiers in Bioengineering and Biotechnology, 2022)
(R)-p-chlorophenyl-1,2-ethanediol (pCPED) is an important intermediate for the synthesis of (R)-Eliprodil that is widely applied in the treatment of ischemic stroke. To prepare (R)-pCPED with high enantiomeric excess (eep) and yield via the enantioconvergent hydrolysis of racemic styrene oxide (rac-pCSO) at high concentration, the bi-enzymatic catalysis was designed and investigated by a pair of epoxide hydrolases (EHs), a mutant (PvEH1Z4X4-59) of Phaseolus vulgaris EH1 and a mutant (RpEHF361V) of Rhodotorula paludigena RpEH. Firstly, the maximum allowable concentration (MAC) of rac-pCSO was confirmed. Subsequently, the addition mode and the weight ratio of two E. coli cells were optimized. Finally, under the optimized reaction conditions: the cell weight ratio 20:1 of E. coli/pveh1z4x4-59 to E. coli/rpehF361V, a simultaneous addition mode and reaction temperature at 25 ℃, 300 mM rac-pCSO in the 100 mL 4% (v/v) Tween-20/phosphate buffer system (100 mM, pH 7.0) was completely hydrolyzed within 5 h, affording (R)-pCPED with 87.8% eep, 93.4% yield and 8.63 g/L/h STY. This work would be an efficient technical strategy for the preparation of chiral vicinal diols at industrial scale.